Simultaneous stochastic volatility transmission across American equity markets - Enzo Weber (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
Information flows across international financial markets typically occur within hours, making volatility spillover appear contemporaneous in daily data. Such simultaneous transmission of variances is featured by the stochastic volatility model developed in this paper, in contrast to usually employed multivariate ARCH processes.The identification problem is solved by considering heteroscedasticity of the structural volatility innovations, and estimation takes place in an appropriately specified state space setup. In the empirical application, unidirectional volatility spillovers from the US stock market to three American countries are revealed. The impact is strongest for Canada, followed by Mexico and Brazil, which are subject to idiosyncratic crisis effects.
Keywords: C32; G15; 330; Stochastic volatility; identification; variance transmission; Börsenkurs; Volatilität; Amerikanisch; Spillover-Effekt; Aktienmarkt; Internationaler Preiszusammenhang; Internationaler Finanzmarkt; Schätzung; USA; Kanada; Mexiko; Brasilien